Expression dynamics of Integrin Subunit Beta 5 in bovine gametes and embryos imply functions in male fertility and early embryonic development. (15th May 2019) - Velho, Ana; Wang, Hongfeng; Koenig, Leslie; Grant, Kamilah E.; Menezes, Erika S.; Kaya, Abdullah; Moura, Arlindo; Memili, Erdogan
Abstract: Integrins have been shown to act as signalling receptors, and they primarily recognise extracellular matrix ligands on the oocyte surface. However, their possible roles in oocyte activation and embryo development are not clearly understood. The objectives of this study were to evaluate expression of Integrin Subunit Beta 5 (ITGβ5) in bovine sperm, oocytes, and early embryos and to ascertain the evolutionary conservation of ITGβ5. To accomplish these objectives, we used western blotting to study expression levels of ITGβ5 protein in sperm and RT‐qPCR to determine expression levels of ITGβ5 transcripts in oocytes and embryos. We have also used bioinformatic analysis to determine the evolutionary conservation of the ITGβ5 protein among various species. Western blotting showed that ITGβ5 protein was detectable in bull sperm. Moreover, results of RT‐qPCR showed that levels of ITGβ5 were significantly higher in the two‐cell embryos, followed by the 8–16‐cell embryos. However, no significant difference in expression levels were noted for the morula and blastocyst stages as compared to MII oocytes. Bioinformatic analysis revealed that ITGβ5 is conserved among various species. We conclude that expression of ITGβ5 in bovine gametes and embryos implies an important role in fertilisation and embryogenesis.